Solid state fermentation of Monascus purpureus in stirred drum bioreactor for production of red pigment from oil palm frond - Mohamad Al Aamin, Razali (2019)
Various concern have been reported regarding the effect of existing synthetic colorant, hence, mass production of natural colorant seems to be a potential alternative in fulfilling the demand of colorant in industries. This research has emphasized on the process capability of stirred drum bioreactor on performing solid state fermentation (SSF) of Monascus purpureus FTC 5357 by using oil palm frond (OPF) for production of red pigment. Seven parameters, namely, initial moisture content (% v/w), inoculum size (spores/mL), peptone concentration (% w/w), initial pH, aeration rate (vvm), loading capacity (% v/v) and agitation programme (cycles/day) were evaluated for red pigment production, biomass, and glucose consumption. One Factor at A Time (OFAT) and two level factorial screening designs were used in the study. Three responses, which were red pigment production, biomass, and glucose consumption have been used as responses to identify the significant factors affecting the SSF process. In OFAT studies, the highest pigment production was recorded at aeration rate of 1 vvm (6.09 AU/g) and the lowest production was obtained at 45% of initial moisture content (0.1 AU/g). In two level factorial design experimental studies, the highest pigment production was 71.86 AU/g by incorporating 75% v/w of initial moisture content, 108 spores/mL of inoculum size, initial pH of 4, aeration rate of 1.21 vvm, loading capacity of 35 % v/v and agitation programme of 6 cycles/day. The most significant factor contributing to the red pigment production was initial moisture content, with F-value and p-value of 46.54 and 0.0002, respectively, followed by inoculum size, with F-value of 14.12 and p-value of 0.0071, respectively. Similar observation also occurred for biomass, shows that highest contribution from initial moisture content with F-value of 55.07 and p-value of 0.0051, followed by peptone with F-value of 20.47 and p-value of 0.0202, respectively. In conclusion, this work demonstrated the potential of using stirred drum bioreactor and OPF substrate in producing higher yield of red pigment production (71.86 AU/g) compared to shake flask fermentation (2.3 AU/g).